Equipoise and the Ethics of the Canadian Lung Volume Reduction Surgery Trial study: Should There Be a Randomized, Controlled Trial to Evaluate Lung Volume Reduction Surgery? - John D Miller; Michael D Coughlin; Lori Edey; Patricia Miller; Yasmin Sivji (Canadian Respiratory Journal)
The physical improvement is so great following lung volume reduction surgery that there is growing opinion that a randomized, controlled trial is unnecessary. A randomized, controlled trial, it is argued, would deprive those patients randomly assigned to the nonsurgical treatment arm the 'benefit' of lung volume reduction surgery. Entering a trial in which one arm leads to a surgical intervention and the other to best medical management also poses a variety of ethical difficulties. If one is to be offered surgery, there must be perceived benefit because the physician has an obligation to offer the best possible treatment for his or her patient. If a patient agrees to have surgery, the expectation is that surgery would help. Thus, a patient randomly assigned to the medical arm of a trial may easily believe that he or she is being deprived of surgery that may help them. This paper illustrates this dilemma using the Canadian Lung Volume Reduction Surgery Trial. The authors discuss the concept of 'equipoise' in three dimensions, adding community equipoise to theoretical equipoise and clinical equipoise earlier described by Freedman. The paper concludes that the Canadian Lung Volume Reduction Surgery Trial needs to continue because of the clinical equipoise that drives it.